2012
DOI: 10.3109/14767058.2012.678438
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical outcome in women with self-prepared birth plan

Abstract: Women presenting with a birth plan, compared to an age-, parity- and gestational week- matched control group are less likely to undergo a cesarean section, more likely to have first and second degree perineal tears and more likely to use an epidural. The paucity of data and the mis-concepts of medical staff suggest that larger prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
5
13
1
1
Order By: Relevance
“…One might even argue against using birth plans in the absence of better outcome scores. However, international literature is showing mixed results and international organizations (World Health Organization and National Institute for Health and Care Excellence) and national guidelines advocate its use…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One might even argue against using birth plans in the absence of better outcome scores. However, international literature is showing mixed results and international organizations (World Health Organization and National Institute for Health and Care Excellence) and national guidelines advocate its use…”
Section: Discussionmentioning
confidence: 99%
“…Some report that women with a birth plan have an improved childbirth experience and are more satisfied, possibly correlating with the number of fulfilled birth plan requests . Women with a birth plan feel more in control during labor, more often have vaginal births, and have a more physiological birth process . There are mixed results in women with a birth plan on the use of an epidural .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no statistically signifi cant differences in cesarean rate (17% in the birth plan group versus 12% in the group without a birth plan). Hadar, Raban, Gal, Yogev, and Melamed (2012) conducted a retrospective study of the outcomes of women with self-prepared birth plans in Israel. They found that these women were less likely to undergo a cesarean birth when compared to women who did not prepare a birth plan (9.3% versus 19.5%).…”
Section: Cesarean Birthsmentioning
confidence: 99%
“…Again, no interviews with the patients were conducted to confi rm this supposition. Hadar et al (2012) reported that of 91.6% of women requesting no episiotomy, 34% received one. Of 46% of women requesting no epidural, 27% received one.…”
Section: Honoring Requestsmentioning
confidence: 99%